2(3y+1)=14+3y

Simple and best practice solution for 2(3y+1)=14+3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3y+1)=14+3y equation:


Simplifying
2(3y + 1) = 14 + 3y

Reorder the terms:
2(1 + 3y) = 14 + 3y
(1 * 2 + 3y * 2) = 14 + 3y
(2 + 6y) = 14 + 3y

Solving
2 + 6y = 14 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
2 + 6y + -3y = 14 + 3y + -3y

Combine like terms: 6y + -3y = 3y
2 + 3y = 14 + 3y + -3y

Combine like terms: 3y + -3y = 0
2 + 3y = 14 + 0
2 + 3y = 14

Add '-2' to each side of the equation.
2 + -2 + 3y = 14 + -2

Combine like terms: 2 + -2 = 0
0 + 3y = 14 + -2
3y = 14 + -2

Combine like terms: 14 + -2 = 12
3y = 12

Divide each side by '3'.
y = 4

Simplifying
y = 4

See similar equations:

| (4a^2+9b^5)-(-2a^2-6b^5)= | | 18-6k=-7(2+2k) | | 3sinx+4cosx=1 | | 666+x=1 | | 3x+y=252.19 | | 9x^2+7=385 | | .75(3x-16)+.75x=5.33333333333 | | -17-5n=6(2+5n)+6 | | 8x^2=4x-1 | | 4x+4-x-1=1 | | Ln(7x-1)=3 | | 5x^2-9=11 | | 3x+2=10x+12 | | -4x+18=-6(3x-3) | | y=32x+25 | | 4(3-u)=-4u-12 | | 10x+4y+5z-5x+2z-7y= | | x+y+z=-7 | | f(x)=5x^2-10x+6 | | 5x^2-3x+18=5x^2+7x-12 | | x-9=2(x-1) | | 3/5x+4/9=10/3 | | 3x/4+2/3=2 | | 3x/4+2/3= | | 5x^2-1x-12=0 | | 3=1.7x | | 5x-3(x-4)=-2+5x-1 | | 0.75(5x-4)=0.5(4x+3) | | 2(x+2)+2(x+4)=26 | | 53c-23=23s | | 4x=5+5x | | 6(4s+3)=114 |

Equations solver categories